2ReLogCarChain using blockchain technology for carbon footprint tracking and monitoring - Fernando, Yudi; Shaharudin, Muhammad Shabir; Herwin, Ika Sari Wahyuni (2021)
The company can monitor the carbon activities using 2ReLogCarChain app with integrated systems. The integration monitoring systems of carbon emission among supply chains networks is not available in the markets. This product can be an alternative solution. Blockchain technology has a high level of security and cannot be hacked. It can be used to support the integration of energy production, utilization, transmission, and storage so that every carbon footprint activity and carbon trading transaction can be tracked and no data can be manipulated.